Food Waste Issue for Enriching Biology Topic: A Case Study at Adiwiyata School - Putri Setioningrum; Agung Wijaya Subiantoro (Postgraduate, University of Mataram, 2023)
The purposes of this study were to find out students' learning experiences on environmental change topic and teachers' views about the potential utilization of food waste issue for the topic. This was a descriptive research that carried out using case study method. The data were collected using questionnaire as well as interviews and analysed descriptively. The results showed that although students have had good learning experience on the topic, however, the issue of food waste has not been discussed, and Â this finding is in align with teachersâ€™ view. Despite of the issue had not been applied as the main context for the environmental change topic, nevertheless, the teachers strongly suggested that the food waste issue potentially useful to be implemented for the topic. Considerations of the implementation are further discussed in this paper.